Social and Environmental Disclosure in Saudi Companies - Al-Gamrh, Bakr Ali Ali (2010)
There is a growth in demand by stakeholders for companies to demonstrate greater transparency on their social and environmental performance. Few studies have been conducted in Saudi Arabia on the area of voluntary disclosure. The present study aims to evaluate the current level of social and environmental disclosure (SED) and to investigate the influence of the variables (size, industry, sector, age, capital raised, and audit firm size) on the general level of social and environmental disclosure in the nonfinancial companies in Saudi Stock Market (SSM). The disclosure index is constructed of 25 items to evaluate the level of disclosure in the 2008 annual reports of all the 93 nonfinancial companies in Saudi Stock Market. The relationships between the disclosure level of the six variables are investigated using ordinary least square regression model. Results show that the level of social and environmental disclosure level is very low for Saudi nonfinancial listed companies. Company size and sector are found to be significantly associated with the level of disclosure. However, the remaining variables are not significantly correlated with disclosure level. This study makes a positive contribution to enhance general knowledge of SED practices and can help Saudi authorities to enforce new policies toward social and environmental reporting.